Efek Hepatoprotektif Sari Belimbing Manis Terhadap Kadar SGPT: Studi Awal Terhadap Tikus yang Diinduksi Parasetamol Dosis Toksik - Amatillah, Hana; Ediningsih, Endang; Hikmayani, Nur Hafidha (Nexus Biomedika, 2013)
Background: Star fruit is a good source of natural antioxidants which can prevent oxidative damages and modulate reactive free-radicals. However, no study had been carried out so far on the hepatoprotective effect of star fruit. This research aimed to study the hepatoprotective effect of star fruit juice on SGPT level in paracetamol- intoxicated rats. Methods: This was a laboratory experimental study with posttest only controlled group design. A total of 30 white male, Wistar rats (Rattus norvegicus), aged 2-3 months and weighed 160-200 grams was assigned into five groups. Normal group and negative control group were administered distilled water, while positive control group was administered Curcuma® (3.6 mg/200 g bw). The treatment group 1 and 2 were administered star fruit juice at concentration of 50% and 100%, successively. This study was performed for 14 days. In the last 3 days, all groups except normal group were induced by paracetamol at toxic dose (291.6 mg/200 g BW) an hour after the treatment of star fruit juice (for treatment group 1 and 2) was done. Blood samples were collected from retro-orbitalis venous to measure SGPT levels. The data were analyzed statistically using one-way ANOVA followed by LSD test. Results: The analysis of SGPT with one-way ANOVA showed a significant difference across all groups. Further, the LSD tests of SGPT level showed significant differences between negative control group (182.5 U/L ± 14.0) and the two star fruit groups (p values <0.001). SGPT mean in treatment group 1 (87.0 U/L ± 14.1) and treatment group 2 (91.7 U/L ± 14.9) also differed from those of positive control (67.1 U/L ± 5.5, p=0.008) and normal group (53.8 U/L ± 8.6, p=0.002). There was no significant difference between two groups treated with star fruit juice (p=0.511). Conclusions: Star fruit juice at concentration of 50% and 100% significantly inhibited the elevation of SGPT levels in paracetamol-intoxicated rats. Keywords: Star fruit juice, SGPT, paracetamol, rats